Guia do centro de - Muriel Reis dos Santos Machado (2019)
Before heading off into the unknown, a traveler studies routes, determines places of interest and looks up for appealing images with one particular goal: select a destination. Among these presets, certain images prevail in relation to others, suggesting possible paths. To reach the center of the peregrination, the traveler may feel the need to use a guide that shows the way. The current research has its starting point in courses carried out between neighborhoods in Belo Horizonte, São José and Florianópolis. From these experiences, emerged the interest to create a publication that approached the language present in tourist guides. The Guia do Centro de was elaborated from the appropriation of parts of different guides and also counts on authorial images and texts. In this direction, the search for a center, for a precise target in a travel, became theme for the artistic production, interested in the ample interpretative possibilities attached to this term. More than stipulating routes that orient the reader through space, the Guia do Centro de guides paths through the universe of images. Through the five essays present in this dissertation, comments are made on some of the images that were determinant to produce the guide.